Digestion of sweet potato (Ipomoea batatas (L.) Lam) foliage in pigs. In situ digestibility measured with mobile nylon bags - D?az, Ivonne; Gonz?lez, C.; Reyes, Julio; Delgado, E.; Ly, Julio (Cuban Journal of Agricultural Science, 2012)
The in vivo and in situ rectal digestibility of sweet potato foliage meal was studied through mobile nylon bags. Four pigs of 40 kg were used, canulated in duodenum and fed maize/soybean diets, partially substituted with 0, 10, 20 and 30 % of sweet potato (Ipomoea batatas (L.) Lam) foliage meal, according to a Latin squeare design 4 x 4. There was no significant effect of the treatment on the in vivo rectal digestibility of sweat potato foliage in the pigs. The diet supplied only influenced significantly (P < 0.05) on the rectal digestibility of the OM measured in in situ. Coincidence was found in the rectal digestibility of the DM (49.4 and 50.2%), nitrogen (N) (44.7 and 45.4%) and the energy of sweet potato foliage (45.6 and 46.7%), when the nutritive value was measured in vivo and in situ. It is suggested that the nutritive values of sweet potato foliage diets can be determined in mouth-rectum of pigs by in vivo and in situ procedures differently, through the technique of mobile bag. Key words: swine, digestion, ileum, rectum, foliar sweet potato.